2013
DOI: 10.1093/abbs/gms112
|View full text |Cite
|
Sign up to set email alerts
|

SREBP: a novel therapeutic target

Abstract: Sterol regulatory element-binding proteins (SREBPs) are major transcription factors regulating the biosynthesis of cholesterol, fatty acid, and triglyceride. They control the expression of crucial genes involved in lipogenesis and uptake. In this review, we summarize the processing of SREBPs and their regulation by insulin, cAMP, and vitamin A, and the relationship between miRNA and lipid metabolism. We also discuss the recent functional studies on SREBPs. These discoveries suggest that inhibition of SREBP can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 88 publications
5
73
0
5
Order By: Relevance
“…Idh1, as well as the mevalonate pathway, is sterol-controlled and activated by sterol regulatory element binding proteins (Srebps) (Shechter et al, 2003). Srebps are the key enzymes of cholesterol and fatty-acid biosynthesis and work as cellular cholesterol sensors as part of the ER membrane (Xiao and Song, 2013). It has been shown that the establishment of HCV infection is inhibited by blocking the Srebp pathway (Olmstead et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Idh1, as well as the mevalonate pathway, is sterol-controlled and activated by sterol regulatory element binding proteins (Srebps) (Shechter et al, 2003). Srebps are the key enzymes of cholesterol and fatty-acid biosynthesis and work as cellular cholesterol sensors as part of the ER membrane (Xiao and Song, 2013). It has been shown that the establishment of HCV infection is inhibited by blocking the Srebp pathway (Olmstead et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, FFA levels were not significantly changed in palmPrRP31-treated rats on the HF diet. Despite this, the liver mRNAs of the enzymes catalyzing the de novo synthesis of fatty acids, Acaca and Fasn, were reduced significantly and in parallel with a reduction in the mRNA of Srebp1, their common transcription factor (Xiao & Song 2013). The precise mechanism of the palm-PrRP31 attenuating effect on lipogenesis in the liver is not known, but a similar effect was shown in our previous study in DIO mice, where a 2-week-long palm-PrRP31 treatment attenuated the liver mRNAs of Acaca, Fasn, and Srebp1 (Maletinska et al 2015) as well.…”
Section: Figurementioning
confidence: 99%
“…The loss of PCSK9 function may stabilize LDLR, minimizing the potential deleterious effects caused by loss of LDLR expression by SREBP-2. The idea of targeting SREBP-2 as a means to help treat hypercholesterolemia is beginning to gain traction ( 81 ). Recently, Moon et al ( 82 ) showed that siSCAP-treated mice showed reduced SREBP-2 expression, but maintained a steady-state LDLR level, most likely due to a reduction in PCSK9 expression.…”
Section: Fig 12mentioning
confidence: 99%